Couple's experiences on disclosure of HIV-positive status at Thulamela B Clinic, Vhembe, Limpopo Province - Maluleke, Tsakani Millicent (My University, 2015)
Purpose of the study The purpose of this study was to investigate the experiences of couples on disclosure of their HIV-positive status to each other. Research methodology Qualitative, Phenomenology, exploratory descriptive and contextual research was conducted to identify the experiences and to determine the strategies that address non-disclosure of couples on their HIV-positive status. The population comprised 12 participants (six (6) couples). Purposive sampling was used to select eight (8) participants (four (4) couples) who participated in the study. Semi-structured interviews were used to collect data until data saturation was reached. Study findings Data were analysed using Tesch’s open-coding method. Five themes emerged, namely, fear of being HIV-positive, disclosure of HIV-positive status is a difficult process, acceptance of HIV-positive status, relations between partners post knowledge of HIV-positive results and encouragement pertaining to disclosure of HIV-positive status. Strategies were developed to address the experiences identified. Recommendations were made for the Department of Health, clinic staff, future researchers, patients and community members. Conclusion Although couples disclosed their status to one another disclosure was found to be a difficult process. Acceptance of HIV status was also found to be one of the challenges that led to delayed disclosure of the status. Support system from both family and community is a very important factor which might increase HIV status acceptance and disclosure from couples. Keywords: Couples, experiences, disclosure, HIV-positive status.
Thesis (M.Sc.) -- University of Limpopo, 2016
Keywords: Couples; Experiences; Disclosure; HIV-positive status; HIV (viruses) -- South Africa -- Limpopo.; HIV-positive persons